Meningkatkan Kemampuan Berpikir Siswa Melalui Problem Based Learning dalam Bingkai Kurikulum Pendidikan Agama Kristen - Asni Darmayanti Duha; Fernistriadi Daeli; Linia Gulo; Meiman Fajar Syahputra Hulu (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2026)
Christian religious education learning is not merely taught to students, but also has an impact in improving students' thinking skills. Within the framework of Christian religious education, learning design is often neglected by Christian religious teachers so that the learning process is only academic achievement without any practical achievement. To implement problem-based learning in Christian religious education learning, good methods and designs are needed, so that the learning concept can improve students' thinking skills. Therefore, the objectives of this study consist of: first, to explain and describe the steps to improve students' thinking skills. Second, to explain and describe how to apply problem-based learning (PBL) within the framework of the Christian religious education curriculum so that learning objectives can be achieved well. This study uses a library research method (literature study). Based on the results of the research study, the application of problem-based learning (PBL) through Christian religious education within the curriculum framework is able to improve students' thinking skills with indicators: student orientation to problems, organizing students to learn, directing individuals or groups to new experiences, presenting work or findings, and conducting analysis and evaluation in the problem-solving process, as well as active student involvement in the learning process.